Affirmation of the Legal Status of Taxpayers in Montenegro - Sra Božović (Journal of Central Banking Theory and Practice, 2016)
Public needs cannot be adequately funded without a clear and legally based affirmative legal status of taxpayers. The promotion and protection of their rights and regular fulfilment of tax obligations by taxpayers is the basis of fiscal and financial stability of the country and other public collectivities. It is essential for Montenegro to overcome the traditional gap between taxpayers and tax administration through their partnership. At the same time, we must not jeopardize the basic purpose of taxation - legal and timely payment of taxes. Simple and stable tax regulations and a non-discriminating and subtle approach to building tax discipline and development of tax morale should serve that purpose.
Keywords: H20; K34; 330; improvement and protection of taxpayer rights; fulfilment of tax obligations; functional legal status of taxpayers; country and taxpayer partnership.